Optimisation of the rotary friction welding process of titanium alloy rods - Zulu Mthobisi (EDP Sciences, 2021)
This paper presents a study on the performance behaviour of friction welded titanium alloy rods. The Ti6Al4V alloy rods were friction welded with continuous-drive friction welding using different combinations of process parameters. The welding speed ranging from 1600 to 2700 RPM and the applied pressure ranging from 25 to 140 MPa were utilized for the welding process. The weld joints and the parent material were examined for microstructure characterisation, Vickers hardness and tensile properties. The microstructure of the weld joint revealed fine equiaxed grains with complete recrystallization. The presence of martensitic grains was obtained at process parameter combinations of low welding speed and high pressure. The tensile tests conducted revealed that the weld joints of low speed and high pressure had improved tensile properties when compared to that of the parent material. The ultimate tensile strength of 1040 MPa with the elongation of 26.5 % was obtained at a speed of 1900 RPM and 80 MPa pressure. The micro-hardness tests revealed an increase in hardness across all the weld zones when compared to the parent material, with the maximum hardness obtained at the weld nugget. Further study was conducted to evaluate the effect of parameters on the weld joint integrity.